Excisional goniotomy vs trabecular microbypass stent implantation: a prospective randomized clinical trial in eyes with mild to moderate open-angle glaucoma. Issue 8 (August 2020) - Falkenberry, Suzanne; Singh, Inder Paul; Crane, Charles J.; Haider, Mohammed Ali; Morgan, Michael G.; Grenier, Christopher P.; Brubaker, Jacob W.; Balasubramani, Goundappa K.; Dorairaj, Syril
Abstract : A prospective RCT comparing 12-month outcomes of KDB vs iStent, both in combination with phacoemulsification, demonstrated that excisional goniotomy with KDB might offer a higher probability of patient-specific surgical success. Abstract : Purpose: To compare reduction in intraocular pressure (IOP) and IOP-lowering medication in eyes undergoing excisional goniotomy with Kahook Dual Blade (KDB) vs iStent microbypass implantation, both combined with phacoemulsification, in eyes with mild to moderate open-angle glaucoma (OAG). Setting: Nine practices in the United States. Design: Prospective, randomized, active-controlled, parallel-group clinical trial. Methods: Eyes were randomized to KDB-Phaco or iStent-Phaco group. Demographics, corrected distance visual acuity, IOP, IOP-lowering medications, and adverse events were collected at baseline and at day 1, week 1, and months 1, 3, 6, and 12 postoperatively. The primary outcome measure was the proportion of eyes at 12 months with IOP reduction of 20% or greater or IOP medication reduction of 1 or more compared with baseline. Results: For this study, 164 eyes of 164 patients were analyzed (82 in each group). Mean IOP was reduced at 12 months compared with baseline from 18.5 (standard of error 0.4) to 15.4 (0.4) mm Hg in the KDB-Phaco group and from 18.5 (0.3) to 16.1 (0.4) mm Hg in the iStent-Phaco group ( P = .24). Mean IOP-lowering medications were reduced from 1.3 (0.1) to 0.3 (0.1) in the KDB-Phaco group and from 1.4 (0.1) to 0.4 (0.1) in the iStent-Phaco group ( P = .17). Among study completers, the primary outcome was attained in 74 (93.7%) of 79 patients of KDB-Phaco eyes and 65 (83.3%) of 78 patients of iStent-Phaco eyes ( P = .04). Both procedures had similar safety profiles. Conclusions: Both procedures lowered both IOP and the need for IOP-lowering medications effectively and safely in eyes with mild to moderate OAG and cataract. Significantly, more KDB-Phaco eyes than iStent-Phaco eyes met the primary outcome of 20% or greater IOP reduction or 1 or more medication reduction at 12 months.